Study on the stability of hydrolyzed sago starch - Muhamad Firdaus, Bin Ismail. (Universiti Malaysia Sarawak (UNIMAS), 2008)
The hydrolyzed sago stan:h cannot be kept for a long term because the concentration of glucose will cbange and it will influence the fennentation process. The objective of this study is to find out the most suitable storage temperature to maintain the stability of hydrolyzed sago starch in tenn of glucose concentration. The enzymes used for sago hydrolysis were Tennamyl-120L (thermostable amylase from Bacillus lincheniformis, 120 KNUIg) and DexlIozyme (a mixture of glucoamilase from Aspergillus niger and pulluanase from Bacillus acidopul/ulyticus, 225 AGU/mJ) supplied by Novo Nordisk.In this research, sterile and non sterile hydrolyzed sago stan:h(HSS) samples at the same volume were stored a temperature of 4°C, 25 ·C, and 60 ·C respectively. Analysis of pH and analysis of glucose using glucose analyzer (Bionseosor BF-5) was carried out started day 0 until day 5 of samples storage. The result showed that glucose concentration of non sterile hydrolyzed sago starch stored at 60 ·C can be maintained or even higher compared to another HSS samples.